ANALISIS KARAKTERISTIK DAN PERILAKU WIRAUSAHA KUE BASAH (Studi pada Melati Chatering Jl. Amaliun Medan) - Dindiya Putri (Jurnal Niaga & Bisnis (e-journal), 2014)
The purpose of this study was : ( 1 ) to describe the characteristics of the individual and entrepreneurial attitude Chatering Bed ( 2) analyze the entrepreneurial attitude cake Melati Chatering ( 3) to analyze the relationship between the characteristics of the entrepreneurial attitude Melati Chatering cake . In this study, the method used is descriptive method with qualitative data . Informants in this study were divided into three , namely the key informant Melati Chatering owner , the key informants Melati Chatering son of the owner and informant added that casual employees amounted to 2 Melati Chatering . The results showed that the characteristics of entrepreneurial cake Chatering Melati consists of educational level, personal values​​, age, and work experience have any effect in managing the business. Melati Chatering entrepreneurial attitude consists of bold face risks, creative and innovative, vision and mission, goals, self-confident, independent, active energetic and appreciate the time, positive self-concept, positive thinking, personal responsibility, and receive feedback. Characterize the dominant attitude towards entrepreneurship eleventh Melati Chatering entrepreneurial characteristics. Entrepreneurial characteristics have considerable influence on the eleven traits entrepreneurial attitude. Keywords: Entrepreneurial Characteristics, Entrepreneurial Attitude.